Service Quality, Facilities, and Customer Satisfaction in Public Health Services: The Mediating Role of Individual Emotions - Nurlaela Nurlaela; Umar Syarifuddin; Harlina Liong; Rofiqah Al Munawwarah (Vifada Management and Social Sciences, 2024)
This study examines the role of product innovation and marketing strategies in enhancing the competitiveness of micro, small, and medium-sized enterprises (MSMEs) operating in the confectionery sector. Employing a qualitative descriptive research design, the study draws on primary data collected through in-depth interviews, direct observations, and documentation analysis involving business owners and key stakeholders of Bundang’s Sweet and Sour Candy MSMEs. The findings reveal that continuous product innovation particularly the development of diverse flavor variants and more attractive, functional packaging significantly increases consumer interest and strengthens product differentiation in a highly competitive market. In addition, the adoption of digital-based marketing strategies, including the use of social media platforms and online marketplaces, has proven effective in expanding market reach and improving brand visibility. The study further demonstrates that the integration of product innovation and targeted marketing strategies creates a synergistic effect that enhances competitive advantage and supports sustainable market growth. These results highlight the strategic importance of aligning innovation capabilities with digital marketing practices to improve MSME resilience and performance. This research contributes to the literature on MSME competitiveness by providing empirical insights into how innovation-driven products and digital marketing can jointly strengthen market positioning. Practically, the findings offer valuable guidance for MSME practitioners and policymakers in formulating strategies to enhance competitiveness in increasingly dynamic and competitive business environments.